Understanding Perceptual Illusion in Children with Special Needs: A Comparison - Dr. Sarah Mufti; Aqsa Chaman; Zanub Ansari (Research Journal of Psychology, 2025)
Purposes: The study aimed to investigate perceptual distortion of visual illusion in children with special needs and mainstream school children. Method and Material: A sample of N=54 (17 Down Syndrome, 10 Slow Learner and 27 Mainstream Children) with the age range of 6-14 years (Mage =10, SD = .49) were participated in the present study. Data was obtained from different special education and mainstream schools of Jhelum and Sara-I-Alamgir. Quasi experimental research design was used, and purposive sampling strategy was implemented. Poggendorff illusion experiment (1) was used for measuring visual illusion. Results: There were significant mean age differences on reaction time 1 but non-significant gender differences. Outcome further revealed that there were significant difference in reaction time 3 in mainstream school children and children with special needs. Conclusion: It was concluded that Down syndrome and slow learner were more perceptually distorted on visual illusion then mainstream children.